Handbook of solar radiation - Waltz, Catherine (New York, NY, USA Callisto Reference, 2015)
This book is an outcome of the contributions made by eminent scientists and experts in the field of solar radiation from all over the world. It focuses on the basics of solar radiation. It also discusses ecological impacts of solar radiation. The book covers numerous topics on solar radiation such as measurements and analysis of solar radiation, and also discusses in detail agricultural application - bioeffect. It provides scientific understanding on solar radiation for reference to researchers and students.
Includes bibliographical references.
Keywords: Solar radiation -- Research